Implementation of the Independent Learning Curriculum in Physical Education: Opportunities and Challenges - Tasya, Amalia (Journal of Salutare, 2025)
Physical education has an important role in the Indonesian education system, not only to improve physical fitness but also to build students' character and social skills, the implementation of the Independent Curriculum in physical education brings challenges as well as opportunities. This research aims to analyze the opportunities and challenges of implementing the Independent Curriculum in physical education and formulate strategic recommendations for its implementation. This study uses the Systematic Literature Review (SLR) method by collecting data from various relevant literature, published between 2022 and 2025, the data analysis process is carried out using a thematic approach to identify gaps and patterns in the existing literature. The results of the study show that the biggest challenges in the implementation of the independent curriculum are teacher readiness, limited facilities, and less effective managerial management. However, great opportunities are also found in the development of game-based learning methods, the use of technology, and more innovative project-based approaches. This study suggests improving teacher training, strengthening physical education facilities, and managerial improvements at the school level to ensure that the implementation of the independent curriculum runs effectively and sustainably